2018
DOI: 10.1007/s00405-018-5073-6
|View full text |Cite
|
Sign up to set email alerts
|

A CFD approach to understand nasoseptal perforations

Abstract: The induced NSP only rendered significant flow alterations in noses with preexisting nasal airway obstruction alterations, whereas in nasal cavities considered as normal the creation of a NSP did not produce significant differences between both sides. We strongly suggest that this finding can explain the variety of symptoms and the number of asymptomatic patients bearing NSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The posterior margin of the perforation consistently presented the highest WSS. Burgos et al evaluated the location effects of NSP on the nasal airflow patterns, again using a virtual surgical tool. The NSPs were virtually created on 4 subjects, with 2 patients with healthy noses and 2 non‐NSP patients with nasal obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The posterior margin of the perforation consistently presented the highest WSS. Burgos et al evaluated the location effects of NSP on the nasal airflow patterns, again using a virtual surgical tool. The NSPs were virtually created on 4 subjects, with 2 patients with healthy noses and 2 non‐NSP patients with nasal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Using fluid flow properties such as airflow velocity, wall shear stress, and heat flux, CFD has demonstrated utility in assessment of upper respiratory tract and airway reconstructive procedures . However, most previous CFD studies on NSPs addressed virtual perforations of non‐NSP subjects or involved a single NSP patient model . In our previous CFD analysis of nasal airflow in 10 NSP patients we found that the high wall shear stress along the posterior margin of the NSP may lead to symptomatology.…”
mentioning
confidence: 95%
“…It is widely used in engineering fields such as hydrodynamics [17,18]. Recently, CFD has also been used in the medical field for flow analysis [19][20][21][22][23][24]. We used CFD to understand the blood flow patterns in FAPs to obtain helpful information or clues for performing the PTI procedure [16].…”
Section: Development Of the Pti Methods Based On A Cfd Studymentioning
confidence: 99%
“…Those parameters allow to distinguish between healthy or diseased nasal cavities, and had been used in a number of studies. 16,18 Both parameters R À ϕ were also used in the present work to investigate from an objective approach the relationship between COM and nasal obstruction.…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%
“…In previous articles, the authors had introduced the use of nondimensional parameters 15 based on quantities obtained from CFD analysis and geometric quantities. Those parameters allow to distinguish between healthy or diseased nasal cavities, and had been used in a number of studies 16,18 . Both parameters Rϕ were also used in the present work to investigate from an objective approach the relationship between COM and nasal obstruction.…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%